2018
DOI: 10.1038/s41598-018-34548-8
|View full text |Cite
|
Sign up to set email alerts
|

PMA inhibits endothelial cell migration through activating the PKC-δ/Syk/NF-κB-mediated up-regulation of Thy-1

Abstract: We previously showed that overexpression of Thy-1 inhibited and knock-down of Thy-1 enhanced endothelial cell migration. Here, we used phorbol-12-myristate-13-acetate (PMA) as an inducer for Thy-1 expression to investigate molecular mechanisms underlying Thy-1 up-regulation. Our data showed that increased levels of Thy-1 mRNA and protein in endothelial cells were observed at 14–18 hours and 20–28 hours after PMA treatment, respectively. Treatment with PMA for 32 hours induced Thy-1 up-regulation and inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…However, PMA similarly induced NETs in neutrophils of both mouse strains at 4 h post-stimulation, while LPS inducing higher NETs (Figures 6G, H, 7) with the prominent pro-inflammatory cytokine production (TNF-a and IL-6) (Figures 8A-C) in Fcgr2b-/-than WT cells. Because spleen tyrosine kinase (Syk) and nuclear factor kappa B (NFkB), a downstream signaling of Syk (68), are the possible shared downstream signaling of PMA and LPS (20,21,69,70), these molecules are explored. At 4 h post-stimulation, PMA upregulated Syk only in Fcgr2b-/-neutrophils, while LPS upregulated Syk in neutrophils of both mouse strains (Figures 8D, E).…”
Section: Prominent Apoptosis and Neutrophilmentioning
confidence: 99%
“…However, PMA similarly induced NETs in neutrophils of both mouse strains at 4 h post-stimulation, while LPS inducing higher NETs (Figures 6G, H, 7) with the prominent pro-inflammatory cytokine production (TNF-a and IL-6) (Figures 8A-C) in Fcgr2b-/-than WT cells. Because spleen tyrosine kinase (Syk) and nuclear factor kappa B (NFkB), a downstream signaling of Syk (68), are the possible shared downstream signaling of PMA and LPS (20,21,69,70), these molecules are explored. At 4 h post-stimulation, PMA upregulated Syk only in Fcgr2b-/-neutrophils, while LPS upregulated Syk in neutrophils of both mouse strains (Figures 8D, E).…”
Section: Prominent Apoptosis and Neutrophilmentioning
confidence: 99%
“…As Figure demonstrates, the rottlerin exposure led to a drop in cyclin D1 as early as after 2 hr. This rottlerin effect can be ascribed to the inhibition of the transcription factor Nuclear Factor Kappa B (NFκB), whose nuclear migration is prevented by rottlerin in a number of cells …”
Section: Resultsmentioning
confidence: 99%
“…This rottlerin effect can be ascribed to the inhibition of the transcription factor Nuclear Factor Kappa B (NFκB), whose nuclear migration is prevented by rottlerin in a number of cells. 13,[24][25][26] Since another known NFκB gene target is the antiapoptotic Bcl-2 protein, we also measured its expression levels by Western blotting. As shown in Figure 2, the levels of Bcl-2 decrease progressively after 6-24 hr of rottlerin exposure.…”
Section: Rottlerin Downregulates Cyclin D1 and Bcl-2 Proteinsmentioning
confidence: 99%
“…Therefore, we concluded that both p65 inhibition at the early stage and c-Rel promotion at the late stage might reduce apoptosis more effectively. Phorbol myristate acetate (PMA) is an activator of NF-κB [10,24,25]. In this study, we administered PDTC at the early stage and PMA at the late stage after ICH, and then detected changes in NF-κB activation, subunit expression, apoptosis, and apoptotic factors.…”
Section: Introductionmentioning
confidence: 99%